Research of the technical characteristics of half-pipe snowboarding - Xiao, N.-N.; Gao, J. (China Winter Sports, 2009)
After analyzing the snowboarders' technical motion in half-pipe snowboarding competition,the article finds out that the flip and turn motion are the core of total motion difficulty. In order to better understand the characteristics of flip and turn motion,with the methods of biomechanical theory,on-site observation and documentary information,it has a biomechanical analysis on the flip and turn motion. The results show that the influencing factors on the flip and turn motion relate to the change of turn axis,flip temporal and spatial characteristics,flip angular velocity,moment of inertia,body shape and flying posture. Therefore,it suggests to improve the control of height,velocity and angle in flip and turn motion for an excelsior technical difficulty.